Hubungan Penyakit Ginjal Kronik dengan Derajat Klinis Covid-19 di Ruang Rawat Inap RSUD Al-Ihsan Bandung Tahun 2021 - Tasya Sherina; Yuke Andriane; Sadiah Achmad (Bandung Conference Series: Medical Science, 2023)
Abstract. Chronic kidney disease can increase the risk of death due to COVID-19 infection. It is caused by changes in the immune system, including persistent systemic inflammation and immunosuppression. Apart from respiratory cells, SARS-Cov-2 also attacks other organs, including the kidney where there are proximal renal tubular epithelial cells, glomerular mesangial cells, and podocytes that express ACE2 receptors on their surface which are the targets of COVID-19. This study uses an observational analytic design through a cross-sectional approach. The sampling technique used simple random sampling which met the inclusion and exclusion criteria, with a total sample of 60 taken from secondary data in the form of inpatient medical records. Bivariate analysis was carried out to analyze the relationship between chronic kidney disease and the clinical degree of COVID-19 using the chi-square test. Univariate data analysis showed that the number of Covid-19 sufferers who experienced chronic kidney disease was 30 people (50.0%), Covid-19 sufferers who did not experience chronic kidney disease were 30 people (50.0%) and the clinical degree of Covid-19 was without symptoms and mild symptoms none (0%), moderate symptoms 37 people (61.7%), severe symptoms 9 people (15.0%) and critical symptoms 14 people (23.3%). The results of bivariate data analysis obtained 0.596 (p> 0.05) so that it can be concluded that there is no relationship between chronic kidney disease and the degree of clinical symptoms in Covid-19 patients at Al Ihsan Hospital in Bandung. Abstrak. Penyakit ginjal kronik dapat meningkatkan risiko kematian karena infeksi COVID-19. Hal ini disebabkan oleh perubahan sistem kekebalan, termasuk inflamasi sistemik persisten dan terjadi imunosupresi. Selain sel pernapasan, SARS-Cov-2 juga menyerang organ lain, termasuk ginjal yang dimana terdapat sel epitel tubulus ginjal proksimal, sel mesangial glomerulus, dan podosit yang mengekspresikan reseptor ACE2 pada permukaannya yang menjadi target COVID-19. Penelitian ini menggunakan desain analitik observasional melalui pendekatan cross-sectional. Teknik pengambilan sampel menggunakan simple random sampling yang memenuhi kriteria inklusi dan eksklusi, dengan jumlah sampel 60 yang di ambil dari data sekunder berupa rekam medis pasien rawat inap. Analisis bivariat di lakukan untuk menganalisis hubungan penyakit ginjal kronik dengan derajat klinis COVID-19 menggunakan uji chi-square. Analisis data univariat menunjukan jumlah penderita Covid-19 yang mengalami penyakit ginjal kronik sebanyak 30 orang (50.0%), penderita Covid-19 yang tidak mengalami penyakit ginjal kronik sebanyak 30 orang (50.0%) dan derajat klinis Covid-19 tanpa gejala dan gejala ringan tidak ada (0%), gejala sedang 37 orang (61.7%), gejala berat 9 orang (15.0%) dan gejala kritis 14 orang (23.3%). Hasil analisis data bivariat diperoleh 0.596 (p>0,05) sehingga dapat disimpulkan tidak terdapat hubungan antara penyakit ginjal kronik dengan derajat gejala klinis pada pasien covid-19 di RSUD Al Ihsan Bandung.